Improving Educational Quality through Optimizing the Potential of Educational Institutions in Indonesia - Ismail, Feiby; Daeng Pawero, Abdul Muis; Umar, Mardan (International Journal of Educational Research & Social Sciences, 2021)
The quality of education in an educational institution will be greatly influenced by the potential of educational institutions and the governance system. The existing potential must be optimized to support quality improvement. Likewise, the education governance system will develop well when it is implemented through a good system by professional managers. The system has been designed in detail by the government which was stipulated by the Minister of National Education Regulation No. 19 of 2007 concerning "Education Management Standards by Primary and Secondary Education Units". This regulation was prepared by the government to regulate a good, balanced and sustainable governance system.The problem is determined to what extentthe ability of educational institutions to optimize the potential of the institution and optimizing inputs, processes, outputs and outcomes, starting from planning, organizing, actuiting, and controlling. This paper will discuss the improving educational quality through optimizing the potential of educational institutions in Indonesia in order to achieve shared ideals for a better educational future.